Interacción farmacocinética entre un medicamento y un nutriente (2010)
ABSTRACT: An important subject in pharmaceutical care is the understanding and monitoring of the possibility of pharmacokinetic interaction between a medicine and a nutrient. This can contribute to an appropriate pharmacotherapy and a better nutritional status of the patient. These can be of physicochemical, biopharmaceutical, physiological and pathophysiological nature, which may alter the pharmacokinetic and pharmacodynamic processes of food in different degrees, as well as those of the medicines and their metabolites. This can lead in turn to a change in the efficacy, safety and effectiveness of the medicine, even conducting to toxicity or altering the nutritional value of food in some cases. Health professionals can prevent interactions by means of a coordinated action. The aim of this paper is to review some aspects related to the pharmacokinetic interactions that have major clinical significance in order to make them understood and taken into account by doctors, pharmaceutical chemists, nutritionists and food engineers so as to improve the therapy and quality of life of the patient.